Research on Credible Financial Reporting 1961-99: The Contributions of Professor Nicholas Dopuch - Kinney, William; Libby, Robert (Journal of Accounting Research, 1999)
William Kinney, Robert Libby, Research on Credible Financial Reporting 1961-99: The Contributions of Professor Nicholas Dopuch, Journal of Accounting Research, Vol. 37, Studies on Credible Financial Reporting (1999), pp. 1-15